Упростите выражение: 1) (2а - с) (а - 3с) + а(2с - а) 2) (3х + у) (х + у) - 4у(х - у) 3) (2х - b) (3х + b) +(3b - x) (b + x) 4) (с + 2) (с - 3) - (с + 1) (с + 3) 5) (у - 10) (у - 2) + (у + 4) (у - 5) 6) (а - 5) (а + 1) - (а - 6...
Упростите выражение: 1) (2а - с) (а - 3с) + а(2с - а) 2) (3х + у) (х + у) - 4у(х - у) 3) (2х - b) (3х + b) +(3b - x) (b + x) 4) (с + 2) (с - 3) - (с + 1) (с + 3) 5) (у - 10) (у - 2) + (у + 4) (у - 5) 6) (а - 5) (а + 1) - (а - 6) (а - 1) 7) 2b (b + 4) + (b - 3) (b - 4) 8) 3p (p - 5) - (p - 4) (p + 8)
Ответ(ы) на вопрос:
Гость
1) (2а - с) (а - 3с) + а(2с - а) = 2a^2 - 7ac + 3c^2 + 2ac - a^2= a^2-5ac+3c^2, 2) (3х + у) (х + у) - 4у(х - у)=3x^2 + 4xy + y^2 - 4xy + 4y^2=3x^2 + 5y^2, 3) (2х - b) (3х + b) +(3b - x) (b + x)=6x^2 - bx - b^2 + 3b^2 + 2bx - x^2 = = 5x^2 + bx + 2b^2, 4) (с + 2) (с - 3) - (с + 1) (с + 3)= c^2 - c - 6 - c^2 - 4c - 3 = -5c-9, 5) (у - 10) (у - 2) + (у + 4) (у - 5)= y^2 - 12y + 20 + y^2 - y - 20 = 2y^2 - 13y = = y(2y - 13), 6) (а - 5) (а + 1) - (а - 6) (а - 1)= a^2 - 4a - 5 - a^2 + 7a -6 = 3a - 11, 7) 2b (b + 4) + (b - 3) (b - 4)= 2b^2 + 8b + b^2 - 7b + 12 = 3b^2 + b + 12, 8) 3p (p - 5) - (p - 4) (p + 8)= 3p^2 - 15p - p^2 - 4p + 32 = 2p^2 - 19p + 32.
Гость
Ответы: 1) a^2-5ac-3c^2 2)3x^2-3y^2 3) 5x^2+2b^2+bx Дальше попробуй сам
Не нашли ответ?
Похожие вопросы